+0  
 
0
73
3
avatar

Compute. \[ (50 + 72i)^2 - (50 - 72i)^2 \]

 Dec 20, 2021

Best Answer 

 #3
avatar+115897 
+2

\((50 + 72i)^2 - (50 - 72i)^2\\ =50^2+(72i)^2+(2*50*72i)\quad -[50^2+(-72i)^2-(2*50*72i)]\\ =2*(2*50*72i)\\ =14400i \)

.
 Dec 20, 2021
 #1
avatar
0

The answer is 17200*i.

 Dec 20, 2021
 #2
avatar+13015 
+1

The answer is 14400 i.

 Dec 20, 2021
 #3
avatar+115897 
+2
Best Answer

\((50 + 72i)^2 - (50 - 72i)^2\\ =50^2+(72i)^2+(2*50*72i)\quad -[50^2+(-72i)^2-(2*50*72i)]\\ =2*(2*50*72i)\\ =14400i \)

Melody Dec 20, 2021

13 Online Users

avatar
avatar